2019
DOI: 10.1103/physrevb.99.075155
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-to-spin angular momentum conversion employing local helicity

Abstract: Spin-orbit interactions in optics traditionally describe an influence of the polarization degree of freedom of light on its spatial properties. The most prominent example is the generation of a spin-dependent optical vortex upon focusing or scattering of a circularly polarized plane-wave by a nanoparticle, converting spin to orbital angular momentum of light. Here, we present a mechanism of conversion of orbital-to-spin angular momentum of light upon scattering of a linearly polarized vortex beam by a spherica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 60 publications
(123 reference statements)
0
25
0
Order By: Relevance
“…In striking contrast, high-refractive index (HRI) dielectric nanospheres present strong magnetic and electric dipolar resonances in the visible [5] region, as well as in telecom and near-infrared frequencies [6]. Notably, when the electric and magnetic polarizabilities of the scatterer are identical, at the so-called first Kerker condition [7], the EM helicity is preserved [8][9][10] and the intensity in the backscattering direction is exactly zero [11][12][13]. These anomalous light scattering effects have been exploited in multiple branches of physics ranging from boosting light collection efficiency in plants [14], to dynamic control of cryptographic nanoprints [15], to maximizing the sensitivity of circular dichroism spectroscopy of chiral molecules [16][17][18][19].…”
mentioning
confidence: 99%
“…In striking contrast, high-refractive index (HRI) dielectric nanospheres present strong magnetic and electric dipolar resonances in the visible [5] region, as well as in telecom and near-infrared frequencies [6]. Notably, when the electric and magnetic polarizabilities of the scatterer are identical, at the so-called first Kerker condition [7], the EM helicity is preserved [8][9][10] and the intensity in the backscattering direction is exactly zero [11][12][13]. These anomalous light scattering effects have been exploited in multiple branches of physics ranging from boosting light collection efficiency in plants [14], to dynamic control of cryptographic nanoprints [15], to maximizing the sensitivity of circular dichroism spectroscopy of chiral molecules [16][17][18][19].…”
mentioning
confidence: 99%
“…On the other hand, for cylindrically symmetric particles, the absence of backscattered light follows from the preservation of EM helicity [14][15][16][17][18]. Conservation of helicity has proven crucial in many applications such as enhanced chiral light-matter interactions [19][20][21][22][23][24][25], or in the spin-orbit interactions of light [26][27][28][29][30][31][32]. In this vein, it has been reported that from a relatively simple far-field measurement of the EM helicity at a right angle, the radiation pattern of the dipolar particle is inferable [33].…”
mentioning
confidence: 99%
“…2(e) have a helical phase distribution as a direct consequence of the phase-shifted superposition of azimuthal polarization of the excitation beam and radial polarization emitted by the nanoparticle [23]. Finally, the presented effect is determined by the longitudinal field components, accentuating their importance in the description of light-matter interaction [19,[42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%